Rekonsiliasi dan Pengampunan: Memori Kolektif Umat Kristen terhadap Peristiwa Darul Islam/Tentara Islam Indonesia di Seko Lemo Tahun 1951-1965 - Rumbi, Frans Paillin; Sulle, Yosef (Asosiasi Teolog Indonesia, 2024)
The Darul Islam/Indonesian Islamic Army (DI/TII) rebellion in South Sulawesi (1951-1965) left scars in the collective memory of the predominantly Christian region of Seko Lemo. This study examines how these traumatic memories have shaped local reconciliation processes. Taking a phenomenological approach, we conducted interviews with first- and second-generation survivors to understand the dynamics of Christian-Muslim reconciliation over time. We find that reconciliation emerged organically as displaced communities returned from voluntary refuge, developing through familial bonds, intermarriage, and perpetrator confessions and accounts. While Christians have extended forgiveness based on values like praying for one’s adversaries, the process remains predominantly interpersonal and social in nature. This study therefore posits the theological importance of divine forgiveness—understood as God’s grace extended to flawed humanity—as a fundamental framework for sustained processes of deeper reconciliation that foster collective healing and community restoration.